Property and Authority in Business Enterprise - Dion, Gérard (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1961)
SummaryIn the following essay, the Author analyses the nature of property in the modern business enterprise and the nature of authority. He concludes that, although property may be considered as a legitimate mode of designation of those in authority, it is not the sole foundation. Management's right are not permanently established; they can change and effectively do change with the times and circumstances.